Prinsip Dan Tantangan Fiqh Muamalah Di Era Modern - Siregar, Edi Sahputra (Lembaga Jurnal dan Seminar Universitas Pembangunan Panca Budi, 2023)
In this article, dishonest practices in muamalah (gaining profits without considering the losses of buyers), selling goods that are not in accordance with promotions, and often committing fraud in weighing are common problems. Furthermore, the development of wealth that is exploitative towards other groups often occurs, with profit considered as the main priority. In fact, maintaining the principles of muamalah in a sustainable manner will bring balanced benefits to sellers and buyers. This discussion will descriptively explain the principles of muamalah, and raise the study of principles and principles in muamalah. The provisions and restrictions of muamalah should create benefits for all parties and avoid any harm. For example, the prohibition of usury by Allah is due to the many disadvantages in it, which can even cause systemic destruction in the macroeconomic aspects of society and the state.